2018
DOI: 10.5114/aoms.2017.65319
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of MBL2 and tuberculosis susceptibility: a meta-analysis of 22 case-control studies

Abstract: IntroductionThe association of mannose-binding lectin gene (MBL2) polymorphisms with tuberculosis susceptibility was inconclusive. In this study, a meta-analysis of 22 case-control studies was carried out to assess the effect of MBL2 polymorphisms on tuberculosis risk.Material and methodsA search was performed in Embase, PubMed and Web of Science up to Sep 30, 2015. Odds ratio (OR) and 95% confidence interval (95% CI) were used to assess the association. Statistical analyses were performed using STATA 12.0 sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
0
10
0
4
Order By: Relevance
“…Cao et al analyzed 22 studies to assess the effect of MBL2 polymorphisms on TB risk. The rs1800451 polymorphism was associated with decreased TB risk in both the total sample and in some ethnic groups; in addition, A/O, rs7096206 and rs1800450 were likely only related to risk in some ethnic groups [56]. The analysis did not differentiate between the total sample and PTB subgroups.…”
Section: Discussionmentioning
confidence: 77%
“…Cao et al analyzed 22 studies to assess the effect of MBL2 polymorphisms on TB risk. The rs1800451 polymorphism was associated with decreased TB risk in both the total sample and in some ethnic groups; in addition, A/O, rs7096206 and rs1800450 were likely only related to risk in some ethnic groups [56]. The analysis did not differentiate between the total sample and PTB subgroups.…”
Section: Discussionmentioning
confidence: 77%
“…To our knowledge, this is the first study to report that the rs930507, rs2099902, and rs10824793 polymorphisms can affect TB development in a population of Han Chinese origin. It is worth mentioning that several meta-analysis studies have reported that five MBL2 SNPs (rs1800450, rs1800451, rs5030737, rs7095891, and rs7096206) are associated with an increased or decreased TB risk [22][23][24][25][26]. However, there is insufficient data regarding the role of rs930507, rs2099902, and rs10824793 in TB susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…As revealed in several meta-analyses, the role of MBL in that disease is unclear and inconsistent, apparently reflecting differences in study design, ethnicity and number of patients tested. Although it is generally believed that MBL2 O alleles may contribute to enhanced susceptibility to TB, at least in some populations (87)(88)(89), certain data suggest diverse associations for D, B, and C variants. Tong et al (90) concluded that minor alleles in codons 52 (D) and 54 (B) elevate the risk of developing disease while that in codon 57 (C) has a protective effect (in Chinese population).…”
Section: Lectin Pathway-associated Molecules In Respiratory Infectionmentioning
confidence: 99%